Chemotherapeutic agents in low noncytotoxic concentrations increase immunogenicity of human colon cancer cells - Kaneno, Ramon [UNESP]; Shurin, Galina V.; Kaneno, Felipe M.; Naiditch, Hiam; Luo, Jianhua; Shurin, Michael R. (Springer, 2011)
Background We have recently reported that chemotherapeutic agents in ultra low noncytotoxic concentrations may block the ability of tumor cells to suppress functional activation of dendritic cells (DCs).Methods HCT-116 human colon cancer cells were treated with 0.5 nM paclitaxel (PAC) or 2 nM doxorubicin (DOX) with the aim of defining the immunogenic changes induced by ultra low noncytotoxic concentrations of antineoplastic chemotherapeutic agents. Genetic alterations were screened by DNA micro-array that revealed increased expression of genes involved in antigen processing and presentation, including the heat-shock protein, calmodulin, and proteasome 26 genes. As the proteins encoded by these genes are involved in the cytosolic route of antigen processing machinery, we next evaluated whether PAC and DOX in noncytotoxic concentrations changed expression of MHC class I antigen processing machinery (APM) components in three different colon cancer cell lines.Results Our results showed that PAC and DOX increased the intracellular expression of APM proteins, including calmodulin, LMP2, LMP7, TAP1 and tapasin. The biological significance of modulation of antigen processing and presentation proteins in tumor cells by ultra low nontoxic concentrations of chemotherapeutic drugs was revealed when non-treated and treated tumor cells were used as a source of tumor antigens for the generation of tumor-specific cytotoxic T cells (CTLs) in vitro. We demonstrated that (i) DCs that engulf tumor cells pretreated with noncytotoxic concentrations of chemotherapeutic agents induced CTLs with a higher cytotoxic potential than DCs loaded with nontreated tumor cells, and (ii) CTLs induced by tumor lysate-pulsed DCs killed live tumor cells more efficiently if these tumor cells were pretreated with noncytotoxic concentrations of chemotherapeutic drugs.Conclusions These results demonstrate that chemomodulation of human tumor cells with noncytotoxic concentrations of chemotherapeutic agents increases tumor immunogenicity and results in the generation of more efficient DC vaccines and CTLs, which can be used for cell-based anticancer immunotherapies.
Keywords: MHC class I; Antigen processing; Paclitaxel; Cytotoxicity; Dendritic cells